Floral morphology and anatomy of Dalechampia alata Klotzsch ex Baill. (Euphorbiaceae), with emphasis on secretory structures - Martins,F. M. (2016)
Abstract The morphology and anatomy of the flower of Dalechampia alata, as well as the chemical nature of the exudates secreted in the inflorescence were studied using light microscope. This is the first report showing the presence of colleters in the genus Dalechampia. In the staminate flower occur a group of small secretory glands. The histochemical results indicate that the substance secreted from the glands is lipidic and resinuous in nature, while in the colleters it consists of polysaccharides and lipid-rich substances. The ovule of D. alata are anatropous, subglobose and bitegmic. It presents obturator, micropyle occluded by nucellar beak and meristematic activity in the ovary wall. The secretion produced in the stigmatic and transmitting tissue consists of polysaccharides.